Genome-wide association study in NSAID-induced acute urticaria/angioedema in Spanish and Han Chinese populations. (November 2013) - Cornejo-García, José Antonio; Liou, Lieh-Bang; Blanca-López, Natalia; Doña, Inmaculada; Chen, Chien-Hsiun; Chou, Yi-Chun; Chuang, Hui-Ping; Wu, Jer-Yuarn; Chen, Yuan-Tsong; Plaza-Serón, María del Carmen; Mayorga, Cristobalina; Guéant-Rodríguez, Rosa María; et al.
Aim: Acute urticaria/angioedema (AUA) induced by cross-intolerance to NSAIDs is the most frequent clinical entity in hypersensitivity reactions to drugs. In this work, we conducted a genome-wide association study in Spanish and Han Chinese patients suffering from NSAID-induced AUA.Materials & methods: A whole-genome scan was performed on a total of 232 cases (112 Spanish and 120 Han Chinese) with NSAID-induced AUA and 225 unrelated controls (124 Spanish and 101 Han Chinese).Results: Although no polymorphism reached genome-wide significance, we obtained suggestive associations for three clusters in the Spanish group ( RIMS1, BICC1 and RAD51L 1 ) and one region in the Han Chinese population ( ABI3BP ). Five regions showed suggestive associations after meta-analysis: HLF, RAD51L1, COL24A1, GalNAc-T13 and FBXL7 . A majority of these genes are related to Ca 2+, cAMP and/or P53 signaling pathways.Conclusion: The associations described were different from those related to the metabolism of arachidonic acid and could provide new mechanisms underlying NSAID-induced AUA. Original submitted 7 June 2013; Revision submitted 19 August 2013